2022
DOI: 10.1007/s11239-021-02581-6
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and comparisons of acute stroke in “recovered" to “active COVID-19 and “pre-pandemic” in Qatar database

Abstract: Understanding the relationship of COVID-19 to stroke is important. We compare characteristics of pre-pandemic stroke (PPS), cases in acute COVID infection (CS) and in patients who have recovered from COVID-19 infection (RCS). We interrogated the Qatar stroke database for all stroke admissions between Jan 2020 and Feb 2021 (PPS) to CS and RCS to determine how COVID-19 affected ischemic stroke sub-types, clinical course, and outcomes prior to, during and post-pandemic peak. There were 3264 cases admitted (pre-pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Another study evaluating outcome data of patients with COVID-19 associated stroke revealed a significantly elevated in-hospital mortality compared to COVID-19 patients without stroke (19.4% vs. 6.2%) with an increased risk for the development of cerebral edema, intracerebral hemorrhage, and myocardial infarction [ 82 , 86 , 87 ]. Additionally, COVID-19 associated stroke was associated with higher rates of ICU admission and intubation compared to stroke patients without COVID-19 [ 88 ]. Moreover, Hernández-Fernández et al [ 89 ] revealed that COVID-19 associated stroke patients may exhibit longer hospitalization rates, slower recovery times and unfavorable functional prognosis evaluated by the modified Rankin Scale in over 64% of cases.…”
Section: Introductionmentioning
confidence: 99%
“…Another study evaluating outcome data of patients with COVID-19 associated stroke revealed a significantly elevated in-hospital mortality compared to COVID-19 patients without stroke (19.4% vs. 6.2%) with an increased risk for the development of cerebral edema, intracerebral hemorrhage, and myocardial infarction [ 82 , 86 , 87 ]. Additionally, COVID-19 associated stroke was associated with higher rates of ICU admission and intubation compared to stroke patients without COVID-19 [ 88 ]. Moreover, Hernández-Fernández et al [ 89 ] revealed that COVID-19 associated stroke patients may exhibit longer hospitalization rates, slower recovery times and unfavorable functional prognosis evaluated by the modified Rankin Scale in over 64% of cases.…”
Section: Introductionmentioning
confidence: 99%